The Impact of an Interprofessional Education Experience on Postgraduate Dietetic Students' Self-Assessed Confidence in Their Ability to Identify and Demonstrate Interprofessional Practice Behaviors. Issue 3 (July 2018) - Karamat, Emma; Pole, David; Rahman, Rabia; Toomey, Eileen; Eliot, Kathrin
Abstract : This study looks at the effect of an interprofessional education experience on dietetic students. Engaging dietetic students in interprofessional education improves their confidence to advocate and demonstrate their scope of training and engage in interprofessional collaboration. Quantitative analysis of retrospective pre-/posttest surveys using paired samples t test and Cohen d effect sizes was used to compare participants' confidence in select interprofessional practice behaviors before and after participating in the interprofessional education experience. There were statistically significant improvements in participants' confidence in all interprofessional practice behaviors surveyed ( P < .05). Effect sizes for changes were considered large by Cohen criteria ranging from 1.16 to 1.40.